CHARACTERISTICS BRANDING & BRAND MANAGEMENT IN THE FASHION INDUSTRY - UROŠEVIĆ Snežana; ZAVRŠNIK Bruno (Annals of the University of Oradea: Fascicle of Textiles, Leatherwork, 2014)
Brand allows for market offer to be identified and differentiated from the competitive offers. The very essence of brand is based not only on potential sales figures, but on the philosophy that makes it posssible for a customer to identify with the brand. Faced with the plenty of market offers customers undoubtedly prefer well-known companies and brands, thus minimizing risk and time consuming activities of gaining futher knowledge concerning alternative offers. The consumers often wonder whether the branded goods are more worth from the other, similar goods without any famous trademarks. There are many questions and theories but only one is undeniable: one should never doubt the companies that invest great amount of assets, ideas, talents, love and risk, intend to risk previously stated items with bad design, services or products’ quality. Brand building in textile industry differs from branding of market offers targeting general public. Branding in textile industry requires more focused approach. Fashion companies are facing with bigger challenges when fighting to attract and keep new consumers who are offered new products and markets. In order to create strong brand, it is necessary to possess expert planning and long-term capital investment. Successful brand is actually an excellent product or service, with creatively designed and conducted marketing. Branding has become marketing’s priority, because successful brands achieve higher prices and gain over loyalty, and attract both consumers and financiers. Marketing agents of the successful 21st century brands must be extremely efficient in strategic brand management, which assumes implementation of marketing activities and programmes in order to build brands, as well as brand management to increase its value. Brands and its value must be regarded and recognized as strategic capital.